(untitled) (Interdisciplinary Studies Journal, 2026)
This article presents a theoretical and propositional approach to Greco-Roman education as a foundation for comprehensive and interdisciplinary education in contemporary basic education. Regarding interdisciplinarity, it is based on the premise that the current educational model experiences disciplinary fragmentation, compromising the comprehensive education of students. Therefore, the objective of this study is to demonstrate how the educational principles of Greco-Roman culture can contribute to overcoming this fragmentation, providing the foundation for an integrative and formative pedagogy. The study adopts an interpretive bibliographic methodology, based on authors such as Morin, Nicolescu, Marrou, and Jaeger. The interdisciplinary focus falls on the first two levels proposed by Nicolescu: application and epistemology. The article also proposes a practical planning framework for interdisciplinary school activities. Finally, the proposal indicates possibilities for constructing the unity of knowledge through meaningful experiences that articulate reason, ethics, aesthetics, and practice, such as the dramatization of classical texts, debates on ethics, and practices based on the rhetorical perspective of antiquity. The conclusion highlights that, although challenging, the proposal represents a response to contemporary educational demands, promoting a humanistic, critical, and comprehensive education.